ANALISIS DAMPAK KELEMAHAN SISTEM INFORMASI DAN PENGENDALIAN INTERNAL PADA LEMBAGA KEUANGAN : Studi Kasus PD BPR Bestari Tanjungpinang - Sekar Melati; Putri Dwi Novrina; Diva Aulia Septiana; Mira Mira; Miltha Amelia Sari (RJABM (Research Journal of Accounting and Business Management), 2025)
Financial institutions play an important role in the economy, providing services that support financial transactions and investments, one of which is PD BPR Bestari Tanjungpinang, behind its very important role, it can experience fraud. Fraud is an act of deception or fraud carried out with the intention of benefiting oneself or harming others, this study was conducted to analyze the impact of weaknesses in information systems and internal controls at PD BPR Bestari Tanjungpinang, and to examine how these factors contribute to financial losses and operational disruptions and how to improve internal control using qualitative research methods with a case study approach and literature study. The results of the study revealed that weak separation of duties, internal supervision, and information system security contributed greatly to corrupt practices carried out systematically by bank management and employees. This study emphasizes the importance of strengthening internal control, increasing external supervision, and ethics education for all employees to prevent fraud from recurring in the future.